ULTRASOUND MARKERS OF PROGRESSION OF RIGHT VENTRICULAR DYSFUNCTION: MODERN APPROACHES TO STAGE STRATIFICATION - Kozhyn, Mykhailo; Khodosh, Eduard; Rynchak, Petro (Sworld-Us Conference proceedings, 2025)
The paper addresses the problem of right ventricular dysfunction stratification according to echocardiographic criteria. A three-stage classification of functional impairment progression from subclinical dysfunction to decompensation is proposed. RV strai